Estudio de la aplicación del marketing turístico en la parroquia Timbara, cantón Zamora. - Tapia Montero, Krupskaya Yuksel (2024)
This research allows obtaining data on the current situation of the parish for strengthening and development, taking into account that the parish has a great tourism potential, which allows seeking in a planned and organized way the development of tourism activities by proposing a marketing application. The general objective was to identify the level of application of tourism marketing in the parish of Timbara, canton Zamora, followed by two specific objectives: the first one, Philip Kotler's methodology was applied, which was based on the 4ps of the marketing mix to determine the current state of tourism marketing that has been applied to each tourism product, with this a bibliographic research was carried out, corroborating information from theses, magazines, websites, analysis of the MINTUR files to apply them to the study of tourism marketing, an interview was then conducted with the president of the Timbara parish government and surveys were obtained through the PEA database of the area of influence of the study site, which included the cantons of Loja, Zamora and Yantzaza. In the methodology for the second objective, based on the current information from the first objective, a DAFO matrix was prepared, the results of which establish strategies for designing the proposal for the tourism marketing plan, a check list of the products to ensure that they comply with the guidelines that a marketing mix should contain. Finally, the strategies for the proposal for the application of the tourism development plan are derived. The conclusions establish that tourism services in the parish are limited, in spite of having a great tourism potential manifested in its natural and cultural attractions and potential products.